2011
DOI: 10.1088/0022-3727/44/29/295103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the oscillating photocarrier grating technique

Abstract: In this paper we present a complete theoretical analysis of the oscillating photocarrier grating (OPG) method, starting from the generalized equations that describe charge transport and recombination under oscillating grating illumination conditions. The solution of these equations allows us to implement a calculation reproducing the experimental OPG curves. We study both experimentally and from our calculations the dependence of the OPG curves on different external parameters, such as the applied electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…[6]. We made measurements using both techniques and we were able to obtain the DOS of the aSi:H sample used for these experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6]. We made measurements using both techniques and we were able to obtain the DOS of the aSi:H sample used for these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…[6] we have demonstrated that ω max − 1 is related to some characteristic time of the sample, which can be the dielectric relaxation time (τ diel ) or the small signal lifetime for electrons (τ n ′). We have also shown that the small signal lifetime is related to the density of states at the electrons quasi-Fermi level, E Fn , by the approximate equation…”
Section: Dos Spectroscopy From Opg/mgt Measurementsmentioning
confidence: 94%
See 2 more Smart Citations
“…8,9 Some methods based on making interference between two coherent light beams have also been proposed for this part of the DOS of a-Si:H; 10 in particular, we have recently proposed the combined use of Oscillating Photocarrier Grating (OPG) and Moving Grating Technique (MGT) for this purpose. 11 These methods provide information about the small-signal excess electron lifetime, s n 0 , which is the characteristic time with which the total electron concentration adapts to a small change in the illumination intensity. In recent publications, we have proposed a simple and a more sophisticated formula for assessing the DOS in the conduction band tail (CBT) from measurements of OPG/MGT.…”
Section: Introductionmentioning
confidence: 99%